Description of last instar larva of Gomphus kinzelbachi Schneider, 1984 and new aspects on distribution and habitats in Iran (Odonata: Gomphinae) - Schneider, Thomas; Schneider, Elias; Ikemeyer, Dietmar; Seidenbusch, Richard; Müller, Ole (Zootaxa, 2017)
Gomphus kinzelbachi Schneider, 1984, was described on the basis of a single teneral male captured by B. L. Sage on the Alwand River in eastern Iraq. A detailed redescription of the male and description of the female were published recently. However, the larva of the species has remained unknown so far. In late April 2017 two of the authors (ES & TS) discovered freshly emerged G. kinzelbachi, some of them still on their exuviae, on the upper part of the Zoreh River in southwest Iran (Khuzestãn). Larvae ready to emerge were observed leaving the water and climbing reed stalks. The development from last instar larvae to freshly emerged G. kinzelbachi was observed, some until maiden flight. Five exuviae and two freshly emerged males were collected for further identification and description. Male and female exuviae of G. kinzelbachi are described and compared with exuviae of Gomphus schneiderii Selys, 1850, from Mazandarãn province in Iran. Furthermore, a key is provided to determine the exuviae of four Iranian species belonging to the subfamily Gomphinae: Gomphus kinzelbachi, G. schneiderii, Stylurus ubadschii (Schmidt, 1953), and Anormogomphus kiritshenkoi Bartenev, 1913. In addition, the eastern Mediterranean Gomphus davidi Selys, 1887, is included in the comparison, because it seems to be the sister species of G. kinzelbachi. During the trips to Iran in 2017 eight new populations of G. kinzelbachi on different stretches of the river systems of Marun, Zoreh, Dalaki, Alwand, and Abi Zinkan were detected, enlarging the known range and habitat requirements significantly. The flight period of G. kinzelbachi in Iran is also discussed.